A New Fluorescence Turn‐On Probe for Aluminum(III) with High Selectivity and Sensitivity, and its Application to Bioimaging. Issue 3 (19th February 2015) - Jiang, Yi; Sun, Lei‐Li; Ren, Guang‐Zong; Niu, Xiang; Hu, Wen‐zhou; Hu, Zhi‐Qiang
Abstract The development of novel selective probes with high sensitivity for the detection of Al3+ is widely considered an important research goal due to the importance of such probes in medicine, living systems and the environment. Here, we describe a new fluorescent probe, N′‐(4‐diethylamino‐2‐hydroxybenzylidene)‐2‐hydroxybenzohydrazide (1), for Al3+. Probe 1 was evaluated in a solution of acetonitrile/water (1:1 v/v). Compared with previously reported probes for Al3+, probe 1 can be synthesized easily and in high yield. A Job plot confirmed that probe 1 is able to complex Al3+ in a 1:1 ratio, and the binding constant was determined to be 4.25×108 m−1. Moreover, the detection limit was as low as 6.7×10−9 m, suggesting that probe 1 has a high sensitivity. Common coexistent metal ions, such as K+, Co2+, Ca2+, Ba2+, Ni2+, Pb2+, Hg2+, Ce2+, Zn2+, Cd2+, Fe3+, showed little or no interference in the detection of Al3+ in solution, demonstrating the high selectivity of the probe. Finally, the ability of probe 1 to act as a fluorescent probe for Al3+ in living systems was evaluated in Gram‐negative bacteria, Escherichia coli, and confocal laser scanning microscopy confirmed its utility. The results of this study suggest that 1 has appropriate properties to be developed for application as a fluorescent probe of Al3+ for use in biological studies.